INVESTIGATING THE EFFECTIVENESS OF USING DRAMA AND ROLE-PLAY ACTIVITIES FOR ENHANCING YOUNG LEARNERS’ ORAL COMMUNICATION SKILLS IN ENGLISH - Sodiqova , O (Educational Research in Universal Sciences, 2023)
The study aimed to compare the effectiveness of traditional instruction methods with creative drama activities in improving young learners’ oral communication skills in English. The participants were divided into two groups, with one group receiving traditional instruction and the other group receiving instruction through drama and role-play activities. Information was collected through pretest and post-test scores, which were analyzed using a paired sample t-test to determine any significant improvements in speaking skills between the two groups. Qualitative data were also collected through student feedback and observations during the instructional period, which were analyzed using thematic analysis to identify any patterns or themes related to the students’ experiences with the different instructional methods.